2019
DOI: 10.1002/ecs2.2718
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the birds and the bees: deriving habitat restoration targets from multi‐species occupancy models

Abstract: Riparian corridors can be highly biodiverse but are often degraded by human activities, and are therefore frequent targets of restoration actions. Yet managers often lack clear guidance on how to conserve or restore riparian vegetation structure and composition to promote wildlife biodiversity, due to the difficulty of balancing the needs of multiple species and taxonomic groups. We used independent multi‐species occupancy models to assess the response of riparian bird and bumble bee assemblages, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Please see www.usgs.gov/westernbb for details. More research focusing on the uncertainties around the stressors likely to have the largest effects (pathogens, pesticides, climate, and habitat loss), evaluating the success of various conservation efforts (e.g., Cole et al 2019), and assessing the locations and appropriate taxa level of the two subspecies is urgently needed. In addition, community science data collection efforts such as Bumble bee watch and iNaturalist can be used in model validation and for learning locations of remnant populations.…”
Section: Implications and A Call To Collaborationmentioning
confidence: 99%
“…Please see www.usgs.gov/westernbb for details. More research focusing on the uncertainties around the stressors likely to have the largest effects (pathogens, pesticides, climate, and habitat loss), evaluating the success of various conservation efforts (e.g., Cole et al 2019), and assessing the locations and appropriate taxa level of the two subspecies is urgently needed. In addition, community science data collection efforts such as Bumble bee watch and iNaturalist can be used in model validation and for learning locations of remnant populations.…”
Section: Implications and A Call To Collaborationmentioning
confidence: 99%
“…Occupancy models estimate a species' probability of occurrence across a set of sites and have been used to model associations between bumblebee presence and various landscape and climate characteristics [1,24,25]. Such presence/ absence data are not as information-rich as abundance data, and it is possible for the two metrics to exhibit conflicting patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, canopy openness and floral species richness did influence detection probability. These results suggest that there may be a gap In general, past work has shown that bumble bees tend to be more abundant in areas with greater floral species richness and abundance and lower shrub or canopy cover (Cole et al, 2019;Grundel et al, 2010;Loffland et al, 2017;Steinert et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…As these models are relatively new, they have not been used in many previous bumblebee ecology studies, perhaps also because they require repeat visits to survey sites which necessarily means sampling fewer different sites (under a fixed amount of survey effort). However, even when employed, previous work has not accounted for the potential influence of habitat variables on detection probability, either not including any parameters on detection (Evans et al, 2019) or only including time of year, time of day, or survey effort as predictors of detection (Cole et al, 2019; Loffland et al, 2017).…”
Section: Introductionmentioning
confidence: 99%